Velocity of Pledged Collateral : Analysis and Implications - Singh, Manmohan (Washington, D.C. : International Monetary Fund, 2011)
Large banks and dealers use and reuse collateral pledged by nonbanks, which helps lubricate the global financial system. The supply of collateral arises from specific investment strategies in the asset management complex, with the primary providers being hedge funds, pension funds, insurers, official sector accounts, money markets and others. Post-Lehman, there has been a significant decline in the source collateral for the large dealers that specialize in intermediating pledgeable collateral. Since collateral can be reused, the overall effect (i.e., reduced ?source' of collateral times the velocity of collateral) may have been a USD 4-5 trillion reduction in collateral. This decline in financial lubrication likely has impact on the conduct of global monetary policy. And recent regulations aimed at financial stability, focusing on building equity and reducing leverage at large banks/dealers, may also reduce financial lubrication in the nonbank/bank nexus.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet